Sosialisasi Peran Partisipasi Masyarakat terhadap Pembangunan Desa di Desa Mojopilang Kecamatan Kemlagi Kabupaten Mojokerto - Faqih, Muhammad; Sarbini; Prasetyo, Hascaria Budi; Derta Nur Anita; Jaka Prima; Cindy Alisia Artanty (Subservire: Jurnal Pengabdian Masyarakat, 2025)
Village development is one of the important aspects of community welfare. The purpose of this service is to provide community education about the role of community participation in village development. The method used in this assistance is the Participatory Action Research method. Through the PAR method, this program focuses on education about the role of community participation in the development of Mojopilang Village, Kemlagi District, Mojokerto Regency. The results of this socialization activity are that the participants, who are mainly village officials, are able to understand the role of the community towards village development, providing motivation to the village head as an agent of change in the vanguard of village development.